Answer:
x=−2
Step-by-step explanation: Step 1: Simplify both sides of the equation.
3(x−5)−3=5(x−2)+2x
(3)(x)+(3)(−5)+−3=(5)(x)+(5)(−2)+2x(Distribute)
3x+−15+−3=5x+−10+2x
(3x)+(−15+−3)=(5x+2x)+(−10)(Combine Like Terms)
3x+−18=7x+−10
3x−18=7x−10
Step 2: Subtract 7x from both sides.
3x−18−7x=7x−10−7x
−4x−18=−10
Step 3: Add 18 to both sides.
−4x−18+18=−10+18
−4x=8
Step 4: Divide both sides by -4.
−4x
−4
=
8
−4
x=−2
Answer:
yes it is right
Step-by-step explanation:
Answer:
Hey there !
Under the More button, select View Course Structure.
Find the lesson to view the assessment answers. Click Quiz Answers.
All the assessment questions related to the lesson are found in the pop-up window. To view a question and answer, select a question number.
The experimental probability is the number of specific outcomes divided by the sample size...
P(6)=27/100 (27%)
P(H)=41/100 (41%)
Not sure, but if you meant rolling a 6 AND getting a head then:
P(6 AND H)=(27/100)(41/100)=1107/10000 (11.07%)
#16: Let's clear the fraction on the way to solving this inequality for x. By mult. the given inequality by 2, we'll get -2 (is greater than) x+4. We want x to be positive. So, leave it where it is. Subtract 4 from both sides of this inequality. We end up with -6 (is greater than) x, which is the same thing as x (is less than) -6. What would the graph of that simple inequality look like?
Graph it. (Hint: The graph is a straight dashed line, and you must shade one side of it, but not the other side.